Research Trends in the Field of Emergency Medicine; A Comparative Bibliometric Analysis on Publications Across Journal Quartiles - Farrokhi, Mehrdad; Forouzanfar, Mohammad Mehdi; Hashemi, Behrooz; Hashemi Nazari, Seyed Saeed (Archives of Academic Emergency Medicine, 2024)
Introduction: Quantitative and qualitative evaluations of the publication trends and architecture can be useful for guiding future research agendas of both researchers and journals. This study aimed to investigate the bibliometric characteristics of emergency medicine (EM) researches across different journal quartiles. Methods: A systematic search was conducted in the Scopus database to retrieve published documents from journals in Q1 to Q4 categories (based on Scimago Journal Ranking) from inception to April 2024. The bibliometric analyses were carried out using the Visualization of Similarities viewer (VOSviewer) software. Results: Based on author keywords analysis, we identified 7 (96 nodes), 7 (110 nodes), 6 (89 nodes), and 7 (110 nodes) clusters for Q1 to Q4 categories, respectively. The most frequent author keywords in Q1 to Q4 categories were resuscitation, trauma, COVID-19, and pediatric, respectively. Among the top 10 author keywords in Q1 to Q4 categories, cardiac arrest, disaster, burn, and trauma with average of 19.58, 9.56, 4.92, and 1.61 citations were the most cited topics. Conclusion: This bibliometric analysis highlights that main focus of research in EM researches varies across different journal quartiles. The most commonly studied topics in EM journal categories are resuscitation, trauma, COVID-19, and pediatric.